A Qualitative Examination of Sport Retirement in Former NCAA Division I Athletes - Kelly Barcza-Renner; Amber M. Shipherd; Itay Basevitch (Bowling Green State University, 2020)
Statistics indicate that the overwhelming majority of NCAA Division I college athletes will not continue in their sport professionally (NCAA, 2019). Therefore, there is a need to develop a deeper understanding of the variables that influence college athletes' psychological health and well-being as they transition to retirement. The present study gathered detailed information about 15 former NCAA Division I college athletes' retirement experiences four to five months post retirement. The findings suggested that the former college athletes had varied retirement experiences ranging from negative to positive. All college athletes who reported having a successful retirement transition described having at least one identified support group, stated they accomplished their athletic goals, indicated they had started pursuing other interests, and identified some positive aspects about their lives since retirement. Alternatively, the college athletes who reported having an unsuccessful retirement transition revealed they did not accomplish most of their athletic goals and struggled to identify any positive aspects about their lives since retirement. The findings of this study highlight the diversity in college athletes' retirement experiences that can occur. Although there is still much more to ascertain about athlete retirement, this exploration into college athletes' retirement experiences offers practical implications for athletes, coaches, practitioners, and those who want to provide support for a retiring athlete.